Conhecimento deficiente acerca da HIV/AIDS em adolescentes do sexo masculino - Albuquerque, Jaqueline Galdino (2008)
The prevalence of infections sexually transmitted in adolescents has been presenting high numbers when it comes to the cases of HIV contamination. Among the factors that contribute to the increase of vulnerability the knowledge stands out, sometimes inadequate and inconsistent, what constitutes an important aspect in the adoption of preventive measures against HIV, being the school an important space to investigate what information these adolescents have on this epidemic. Facing this, it was aimed to identify the nursing diagnosis, the deficient knowledge concerning HIV/AIDS in male adolescents. This is a descriptive study of the transversal type with quantitative approach. The population consisted of male adolescents, from 12 to 18 years, of one public school and one private. The sample was composed by 326 students. The data were collected in the months of June and July 2008, through a questionnaire containing the data data referring to the identification of the nursing diagnosis in study. The age averages of the students were of 15.25 and 14.52 years, for thoses in the public and private institutions respectively. Most were single. The diagnosis was identified in 97.2% of the researched, being the inadequate performance in a test the most present defining characteristic. The performance inferior to 80.0% in the indicators used to this evaluation was of 68.4% regarding the knowledge on general aspects of HIV/AIDS; 72.1% to the contamination forms; and the referring percentages to the correct use of the male preservative and the prevention forms were respectively 52.5% and 61.3%. Concerning the referring factors it was frequently found the lack of familiarity with the information resources. Among the means mentioned to the knowledge acquisition on HIV/AIDS, we have the health professionals, the lectures, the hospitals and the teachers. About the searched resources, it was seen that the lectures, the internet, the teachers and the parents are among the most mentioned. The friends were the option of few adolescents. Regarding the referring factor - lack of interest in learning - the students that told never had looked for information justified such conduct mainly because of the lack of opportunity, indifference and because they don’t give importance to the theme. It was concluded that the knowledge deficiencies found were related with the use of the term bearer as reference to the soropositives, the existence of differences between being contaminated and develop or not AIDS, the virus transmission through the sexual act with only one partner without the use of preservative, as well as the contaminated mother to the child, the sexual relationship with vaginal and anal penetration without condom, and through blood donation. About the use of condom, the alternatives that presented smaller percentage of success were referring to the use of lubricants, the storage and the insertion. Therefore, the nursing interventions of educational nature should reinforce the existent knowledge and give priority the found deficits, in a way to focus the nursing actions in the acquisition of favorable results to increase the knowledge of these adolescents regarding HIV/AIDS.